Astragalus polysaccharide alleviated hepatocyte senescence via autophagy pathway - Ting Yao (Kaohsiung Journal of Medical Sciences, 2022)
Abstract Aging is characterized by inevitable organ function decline over time, with consequent body deterioration and increased susceptibility to death. Astragalus polysaccharide (APS) has been reported to have anti‐oxidative, anti‐apoptotic, and anti‐inflammatory properties. We investigated the potential protective effects of APS on hydrogen peroxide (H2O2) induced hepatocyte senescence and identified related mechanisms in L02, Huh7, and LM3 cell lines. Aged female C57BL/6 mice were given APS for 1 week by intraperitoneal injection, and APS provided the strongest protective effect against H2O2‐induced damage at 100 μM. APS reduced the expression of cell senescence markers and alleviated pathological damage in aged mouse liver. APS treatment decreased oxidative stress, apoptosis, NOD‐like receptor protein‐3‐mediated pyroptosis, and maintained mitochondrial homeostasis. Notably, the protective effect of APS was weakened in the presence of chloroquine. APS might enrich autophagy by activating AMP‐activated protein kinase (AMPK) and inhibiting mammalian target of rapamycin (mTOR). In conclusion, APS reduced reactive oxygen species levels, inhibited apoptosis and pyroptosis, and promoted mitophagy via AMPK/mTOR pathway to alleviate hepatocyte senescence in vitro and in vivo.